Epidemiological study of ankle fractures - Mizusaki, Jorge; Santos Prata, Sérgio Damião; Rizzo, Marco; Gonzaga Filho, Luiz Augusto Sampaio; Carneiro, Leandro (Journal of the Foot & Ankle, 2021)
Objective: To evaluate the epidemiological characteristics of patients with fractures in the ankle region. Methods: This prospective, observational, descriptive, and epidemiological study included ankle fractures treated at our service from March 1, 2017 to March 1, 2018. Data were obtained from 150 patients through a detailed questionnaire. Results: The sample, which included 61.33% men, aged mainly between 20 to 30 years; 46.68% were of mixed race, and 41.33% had only completed elementary school. A total of 33.66% of the ankle fractures occurred in the afternoon. According to the Weber classification system, 46.66% were type B fractures. Conclusion: Ankle fractures were more common in men of working age, and were mostly closed fractures in the right lower limb. Level of Evidence IV; Prognostic Studies; Case Series.